READING QUESTION CONSTRUCTION BY ENGLISH TEACHERS: IMPLEMENTING BLOOM’S TAXONOMY IN PADANG SCHOOLS - Meiliza Delviyanti; Sitti Fatimah (English Review: Journal of English Education, 2025)
This study explores the development of written reading comprehension questions by English teachers in junior high schools in Padang, focusing on the use of Bloom's Taxonomy to support higher-order thinking skills (HOTS). Given the importance of English as a foreign and international language, reading comprehension is crucial for students, not only for information retention but also for critical thinking. Using Bloom's cognitive taxonomy as a framework, this study assesses teachers' abilities to formulate questions across three HOTS levels: analysis, evaluation, and creation. Data were collected from four English teachers across three schools, employing qualitative methods, including interviews and test assessments. Results show that while teachers predominantly formulated questions at the analysis level (76%), questions requiring evaluation and creation—skills essential to fostering critical and creative thinking—were significantly lower, at only 15% and 8%, respectively. These findings reveal that although teachers demonstrate some capacity for incorporating analytical questions, there is a need for improvement in crafting questions that challenge students to evaluate and create, aligning with HOTS objectives. Teachers cited challenges such as limited student vocabulary, time constraints, and a lack of in-depth training on Bloom’s taxonomy. This study underscores the importance of targeted professional development to enhance teachers' competence in developing HOTS-oriented questions, thereby fostering students' critical thinking and problem-solving skills.